Deadpool. Vol. 2, The death of Wade Wilson - Ziglar, Cody; Quasarano, Alexis (Deadpool, 2025)
The impossible has happened! Wade Wilson has fallen, and now his daughter Ellie has taken up the mantle of Deadpool. Taskmaster continues her mercenary training, but what Ellie really wants in vengeance. And to get that, she'll need the help of her symbiote dog-"sister," Princess! They're going to kick butt and take names -- but if they can't track down an old friend of Deadpool's, Ellie's career just might end before it ever begins! And how will the regenerating teen degenerate cope with coming face-to-(massive) face with M.O.D.O.K, the Mental Organism Designed Only for Killing? And does dead really mean dead when it comes to the Merc With a Mouth?!